2001
DOI: 10.1080/03014223.2001.9518254
|View full text |Cite
|
Sign up to set email alerts
|

Relative abundance of mammalian predators in the upper Waitaki Basin, South Island, New Zealand

Abstract: An intensive predator trapping programme was implemented in the upper Waitaki Basin, New Zealand from October 1997 to January 1998. The aim of the programme was to prevent increased predation on vulnerable braided river fauna following decline in rabbits due to rabbit haemorrhagic disease (RHD). Fourteen sites were trapped using a standardised method, and trap catch results provided a relative index of predator abundance. In 101 650 trapnights, 1067 hedgehogs, 328 ferrets, 196 cats, 96 rats and 69 stoats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…Our results thus support a limited role for Ferret predation on Lapwing, and potentially other waders, suggesting that, unless a specific problem such as a loss of primary prey is identified (e.g. Keedwell & Brown 2001), resources should not be allocated to mustelid control in order to benefit such species. These results are unusual, however, given the devastating impact of introduced mustelids on many other islands (Craik 1997, Clapperton & Byrom 2005, and may reflect both the current low number of ground-nesting birds compared with previously recorded population sizes on Rathlin (Anon.…”
Section: Effects Of Predator Control On Brood Survivalsupporting
confidence: 51%
“…Our results thus support a limited role for Ferret predation on Lapwing, and potentially other waders, suggesting that, unless a specific problem such as a loss of primary prey is identified (e.g. Keedwell & Brown 2001), resources should not be allocated to mustelid control in order to benefit such species. These results are unusual, however, given the devastating impact of introduced mustelids on many other islands (Craik 1997, Clapperton & Byrom 2005, and may reflect both the current low number of ground-nesting birds compared with previously recorded population sizes on Rathlin (Anon.…”
Section: Effects Of Predator Control On Brood Survivalsupporting
confidence: 51%
“…Corpses were most abundant on roads in suburban and farmed landscapes, and were absent between Taupo and Waiouru, and between Haast and Westport. They were also absent from State Highway 8 through the Mackenzie Basin, in contrast to their abundance along vegetated margins of braided rivers there (Keedwell & Brown 2001). Micol et al (1994) found that distance from towns, and indices of badger (Meles meles) and earthworm (Lumbricus spp.)…”
Section: Densitymentioning
confidence: 95%
“…Gorton (1997) estimated hedgehog density at 0.88 animals per hectare in mixed pasture and native bush, but considered that this was probably an underestimate. Keedwell and Brown (2001) set Fenn and Victor traps at 14 sites in the Mackenzie Basin between 31 October 1997 and 23 January 1998, mainly along the margins of braided rivers. Hedgehogs were the most frequently trapped species.…”
Section: Densitymentioning
confidence: 99%
“…Since stoats are considered to be more serious conservation pests than ferrets or cats (Norbury & Murphy 1996), this shift in the local predator guild could be one of the less desirable consequences of the illegal introduction of rabbit hemorrhagic disease (Norbury & Murphy 1996). Over the last three years, however, predator trapping by Department of Conservation staff in four Mackenzie Basin rivers has not indicated any changes in the predator guild (Cook & Maloney 1999;Cook et al 2000;Keedwell & Brown 2001).…”
Section: Population Dynamicsmentioning
confidence: 99%